TRANSLATION (ÜBERSETZUNG) AND MEDIATION (SPRACHMITTLUNG) OF GERMAN SOCIO-ECOLOGICAL TERMS - Agranovskaya, I.A. (RUDN Journal of Language Studies, Semiotics and Semantics, 2017)
In recent years ecology has acquired special significance due to environmental deterio-ration and awareness of the need for caring attitude towards nature. Solution of environmental problems requires collaborative effort of specialists from different fields of expertise: ecology and natural resource management, economics, sociology, jurisprudence and terminology, since effective communication based on a common terminology base is key to successful cooperation. Some terms, however, have no exact analogues in other languages. Some terms lose their meaning in literal translation (“energy crops”, “invisible energy carriers”), while others (mostly one-word), consisting of several components, translate into a complete phrase (Naturerfahrungsraum - “space to gain experience with nature”). The article deals with German and international socio-ecological terms, which are difficult or impossible to literally translate into Russian while retaining the original meaning. The list also includes several terms that have literal translations (loan translations) into Russian, which do not explain the meanings of the terms to non-experts (“green bridge”, “ecological footprint”), as well as the terms located at the boundary of human ecology and related fields (economics, politics, urban ecology, etc.). The author argues the adviseability of using Sprachmittlung (mediation) instead of Übersetzung (translation) for working with such terms and gives specific examples showing the metaphoricity of German socio-ecological vocabulary (“CNC land insurance”, “safari in a puddle”). Communication of meaning or language mediation (Sprachmittlung) is the subject of this study. The objects of the study are German as well as English (international) socio-ecological terms. Works by E.M. Kakzanova, I.G. Olshansky, Egon Becker and others lay the theoretical foundation of the research. Finally, the author draws conclusions about the peculiarities of communication of meaning of German and English socio-ecological terms.